2024
DOI: 10.9734/ajess/2024/v50i51350
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Tudang Sipulung Integrated Project-based Learning Model to Improve the Character of Mutual Cooperation at the Elementary School Level

Fitri Yanty Muchtar,
Patta Bundu,
. Anshari

Abstract: This research aims to analyze the effectiveness of the Tudang Sipulung integrated project-based learning model to improve the character of mutual cooperation at the elementary school level. This type of research is Research and Development (R&D). The development design model used in this research is the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this research were fourth grade students at PAM Pilot Elementary School. Technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several studies have revealed that the integration of indigenous knowledge and learning activities can enhance students' critical thinking and moral development. Integrating the principles in the Bugis culture, namely "Tudang Sipulung" into learning has proven to be effective in improving students' cooperative character (Muchtar et al, 2024). Besides, technology-based learning models can also incorporate local cultural values to enhance student character (Jamaluddin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that the integration of indigenous knowledge and learning activities can enhance students' critical thinking and moral development. Integrating the principles in the Bugis culture, namely "Tudang Sipulung" into learning has proven to be effective in improving students' cooperative character (Muchtar et al, 2024). Besides, technology-based learning models can also incorporate local cultural values to enhance student character (Jamaluddin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%